MEMBACA DAN MENULIS PERMULAAN: PERAN ORANG TUA DALAM MEMPERSIAPKAN ANAK MENUJU PENDIDIKAN DASAR DI PAUD SAFITRI KECAMATAN SERANG - Risna, Inten; Andini, Andini; Rianti, Rini; Hasanah, Hasanah; Anisah, Anisah; Sumarni, Ani; Fitriyani, Fifi; Rusdianti, Shofia (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service activity aims to provide parents with an understanding of the importance of early literacy and effective ways to stimulate the reading and writing skills of young children. The theme of the activity is "Reading & Writing for Early Childhood", held at PAUD Safitri, Kota Serang, with the Ambassador of Reading from Serang City 2023 as the speaker. This event was attended by 10 parents who focused on understanding and practising early literacy methods. During this activity, parents were introduced to the importance of language and literacy development in children and techniques they can apply at home, such as reading aloud, matching pictures with words, and writing their child's name. The evaluation results showed that interactive and experience-based methods were more effective in increasing children's interest in literacy compared to conventional methods. In addition, parents gained an understanding of the stages of children's literacy development and how to provide stimulation appropriate for their age. The activity also emphasised the importance of a home environment that supports literacy, where children familiar with books and stories are more interested in reading and writing. With this activity, it is hoped that parents will become more actively involved in supporting their children's literacy development enjoyably and effectively.